Provincial ecological well-being performance level measurement and its spatial-temporal evolution analysis in China - Deng, Yuanjian; Ma, Yan; Yang, Xu (Frontiers in Environmental Science, 2022)
Based on the panel data of 30 provinces (autonomous regions and municipalities) in China from 2004 to 2017, this paper used the three-stage super-efficiency SBM-DEA model to calculate the ecological well-being performance (EWP) of provincial capital cities and analyzed its temporal and spatial evolution. The results show that: (①) the improvement of China’s technological level and opening-up level can promote the improvement of ecological well-being performance, while the improvement of environmental regulation, urbanization level, and economic development level can inhibit the improvement of ecological well-being performance (②). After excluding the influence of external environment and random interference, the ecological health performance of the whole country and the eastern, central and western regions has been improved, with the eastern region having the greatest improvement and the central region having the smallest improvement. The performance level of national ecological well-being presents a spatial pattern of “strong in the eastern region, secondary in the central region and weak in the western region” (③). The ecological well-being performance levels of Beijing, Hainan, and Shanghai had always been at the forefront of the country, while those of Ningxia, Inner Mongolia, and Liaoning had been in the bottom three for a long time. The gap between provinces is obvious, but the gap between provinces within the same region is smaller.